Role of endosomal toll-like receptors in immune sensing of Klebsiella pneumoniae - De Gaetano, Giuseppe Valerio; Famà, Agata; Lentini, Germana; Coppolino, Francesco; Venza, Mario; Venza, Isabella; Laganà, Pasqualina; Berbiglia, Alessia; Grasso, Federica; Fiore, Luigi; Teti, Giuseppe; Beninati, Concetta (Frontiers in Immunology, 2025)
Klebsiella pneumoniae is the causative agent of a wide range of antibiotic-resistant infections, including nosocomial pneumonia and neonatal sepsis. We investigate here the mechanisms underlying innate immune recognition of this pathogen by focusing on the role of endosomal Toll-like receptors (TLRs), which sense prokaryotic nucleic acids, in comparison with TLR4, which recognizes the cell-wall lipopolysaccharide component. Lack of functional endosomal TLRs made mice more susceptible to pulmonary infection by K. pneumoniae, in association with reduced production of proinflammatory and chemotactic cytokines and reduced neutrophil recruitment to the lung. This phenotype was as severe as that of TLR4-deficient mice and only moderately milder than that of mice lacking the TLR adaptor MyD88. Notably, macrophages lacking at the same time TLR7, 9 and 13 were more defective than those lacking only TLR9 in their ability to produce proinflammatory cytokines, suggesting a role for the RNA sensing TLR7 and 13 receptors in K. pneumoniae recognition. Collectively, our results unveil the presence of an integrated system of DNA and RNA sensing TLRs that cooperates with TLR4 in immune detection and clearance of K. pneumoniae. These data may be useful to devise alternative therapeutic approaches aimed at stimulating responses against antibiotic-resistant K. pneumoniae strains.